6(9+5x)=54+

Simple and best practice solution for 6(9+5x)=54+ equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(9+5x)=54+ equation:



6(9+5x)=54+
We move all terms to the left:
6(9+5x)-(54+)=0
We add all the numbers together, and all the variables
6(5x+9)-0=0
We add all the numbers together, and all the variables
6(5x+9)=0
We multiply parentheses
30x+54=0
We move all terms containing x to the left, all other terms to the right
30x=-54
x=-54/30
x=-1+4/5

See similar equations:

| 8-m-6-m=2(m-3)-2m | | 132-2s=​4/​3​​s+132 | | -20-7g=1-g | | 1.67e-6=2.5(e-10)-7 | | (y+10)=+10 | | 9x-7=5x+41 | | 40+8m=4(6m+2) | | 4x/8=3/12 | | 1+(7/2a)=(15/2a^2) | | 2m-m-m=3m+1 | | 2/5c+4-1/2c=-9 | | 2+3(2)+3x=11 | | Y+1=-10(x-3) | | (5/4)x=120 | | m=(2m/3)+1 | | a÷7+5÷7=2÷7 | | 1/4x-1/12=1/12x+1/12 | | -6=(3x-12)/3 | | Y=x-5+x=2.65 | | 2x+15=-10 | | (6x-7)(5x=4)=0 | | 3x+4(x+6)=6x-4+x | | -3(3+m)=-9 | | 3m+2(m-4)=-2(m-2)-6 | | x/12+1/3=1/4 | | -(v-1)=-1 | | Y=45x^2-9x | | 3+9x=76 | | 0=-2/3(x)+5 | | 4x^2-100x+525=0 | | 2+2|3s|=12 | | x+21+2x=-4-2x+10 |

Equations solver categories